Diversity of insect flower visitors of cayenne pepper in agricultural landscapes, Banggai, Central Sulawesi - Pramoto Alingan; Mihwan Sataral; Agmal Qodri (Faculty of Agriculture, Tompotika Luwuk University, 2023)
The existence of semi-natural habitats around agricultural land has the potential to support ecosystem services by providing resources for beneficial insects. The study aimed to analyze the abundance, diversity index, and evenness of the insects visiting cayenne flowers. This research was carried out in cayenne cultivation areas in the Banggai Regency. Sampling locations were divided into two categories: cayenne fields close to and far from forests or semi-natural habitats. Insect collection was carried out from June 2022 to August 2022, in the morning and evening, using insect nets. The results showed that 16 families and 52 cayenne flower-visiting insects were identified. Lasioglossum sp.3, Lasioglossum sp.5, Megachile sp.2, ?Parancistrocerus sp. and Rhynchium sp. have a higher abundance than the others. The highest Shannon and Wiener diversity index was found in cayenne fields in Tolisu Village (H'= 2.491), Mansahang (H'= 2.216), Salodik (H'= 2.145), and the lowest in cayenne fields in Kembang Merta Village (H'= 1.211), Dale-Dale (H'= 1.112 ), and Beringin Jaya (H'= 1.149 ). The highest evenness index (E) was found in the fields in Lembah Makmur Village (E= 0.9721) and Mansahang (E= 0.9172), and the lowest was found in cayenne fields in Petak Village (E= 0.3975) and Lenyek (E= 0.4405). The highest species richness was found in cayenne fields in Tolisu (14 species), Salodik (14 species), and Petak (12 species). Cayenne fields in the three villages are close to semi-natural habitats. Our findings show that agricultural land adjacent to semi-natural habitats has increased the species richness of cayenne flower visitor insects. Thus, semi-natural habitats are critical to sustaining insect communities in agricultural landscapes.